A developmental logic: Habermas's theory of social evolution. - Oh, Keunchang (Theoria: A Swedish Journal of Philosophy, 2024)
In the paper, I first consider how his theory of social norms is connected to his theory of social evolution by examining the importance of learning in his theory of both social norms and social evolution. Then I turn to David Owen and Amy Allen's critiques of Jürgen Habermas. My aim is to develop their critique of Habermas by elucidating an important but neglected distinction between the developmental logic and the developmental dynamics in Habermas's theory of social evolution. Drawing on this distinction, I claim that Habermas's theory is problematic in that he underestimates the importance of the developmental dynamics. By introducing the distinction between individual learning and social learning, I also question his account of progress as accumulative experience of learning. This is because, unlike cumulative culture at the level of phylogenesis, individuals ontogenetically experience a kind of non‐cumulative social learning. Unlike cumulative culture, each individual has to undergo a kind of non‐cumulative social learning. The problem is that Habermas conceives the learning process too narrowly such that learning does not guarantee social evolution.